Isolation of ferret astrocytes reveals their morphological, transcriptional, and functional differences from mouse astrocytes - Roboon, Jureepon; Hattori, Tsuyoshi; Nguyen, Dinh Thi; Ishii, Hiroshi; Takarada-Iemata, Mika; Kannon, Takayuki; Hosomichi, Kazuyoshi; Maejima, Takashi; Saito, Kengo; Shinmyo, Yohei; Mieda, Michihiro; Tajima, Atsushi; et al. (Frontiers in Cellular Neuroscience, 2022)
Astrocytes play key roles in supporting the central nervous system structure, regulating synaptic functions, and maintaining brain homeostasis. The number of astrocytes in the cerebrum has markedly increased through evolution. However, the manner by which astrocytes change their features during evolution remains unknown. Compared with the rodent brain, the brain of the ferret, a carnivorous animal, has a folded cerebral cortex and higher white to gray matter ratio, which are common features of the human brain. To further clarify the features of ferret astrocytes, we isolated astrocytes from ferret neonatal brains, cultured these cells, and compared their morphology, gene expression, calcium response, and proliferating ability with those of mouse astrocytes. The morphology of cultured ferret astrocytes differed from that of mouse astrocytes. Ferret astrocytes had longer and more branched processes, smaller cell bodies, and different calcium responses to glutamate, as well as had a greater ability to proliferate, compared to mouse astrocytes. RNA sequencing analysis revealed novel ferret astrocyte-specific genes, including several genes that were the same as those in humans. Astrocytes in the ferret brains had larger cell size, longer primary processes in larger numbers, and a higher proliferation rate compared to mouse astrocytes. Our study shows that cultured ferret astrocytes have different features from rodent astrocytes and similar features to human astrocytes, suggesting that they are useful in studying the roles of astrocytes in brain evolution and cognitive functions in higher animals.